Maternal Protein Intake during Pregnancy Is Not Associated with Offspring Birth Weight in a Multiethnic Asian Population - Chong, Mary Foong-Fong (2015)
Background: Maternal diet during pregnancy can influence fetal growth. However, the relation between maternal macronutrient intake and birth size outcomes is less clear. Objective: We examined the associations between maternal macronutrient intake during pregnancy and infant birth size. Methods: Pregnant women (n = 835) from the Singapore GUSTO (Growing Up in Singapore Towards healthy Outcomes) mother–offspring cohort were studied. At 26–28 wk of gestation, the macronutrient intake of women was ascertained with the use of 24 h dietary recalls and 3 d food diaries. Weight, length, and ponderal index of their offspring were measured at birth. Associations were assessed by substitution models with the use of multiple linear regressions. Results: Mean ± SD maternal energy intake and percentage energy from protein, fat, and carbohydrates per day were 1903 ± 576 kcal, 15.6% ± 3.9%, 32.7% ± 7.5%, and 51.6% ± 8.7% respectively. With the use of adjusted models, no associations were observed for maternal macronutrient intake and birth weight. In male offspring, higher carbohydrate or fat intake with lower protein intake was associated with longer birth length (β = 0.08 cm per percentage increment in carbohydrate; 95% CI: 0.04, 0.13; β = 0.08 cm per percentage increment in fat; 95% CI: 0.02, 0.13) and lower ponderal index (β = −0.12 kg/m3 per percentage increment in carbohydrate; 95% CI: −0.19, −0.05; β = −0.08 kg/m3 per percentage increment in fat; 95% CI: −0.16, −0.003), but this was not observed in female offspring (P-interaction < 0.01). Conclusions: Maternal macronutrient intake during pregnancy was not associated with infant birth weight. Lower maternal protein intake was significantly associated with longer birth length and lower ponderal index in male but not female offspring. However, this finding warrants further confirmation in independent studies.